A Simple Manufactured Hardness Sensor Based on Multi‐Layer Liquid Metal Sensing for Surgical Robotics - Tao Yue; Yuyin Zhang; Yuanjie Gan; Chengzhi Hu; Yue Wang (Advanced Electronic Materials, 2025)
Abstract Tactile information, serving as the most intricate form of data humans gather from the external environment, has long been a significant area of focus for wearable flexible sensors. The advancement of wearable technology and robotics in healthcare has spurred research into integrating thin, compact flexible sensors into robotic systems for mimicking human tactile tissue manipulation during surgery and data collection. Here, a continuous injection method is used to fabricate a multi‐layer liquid metal sensor. By laminating multiple PDMS microfluidic layers, the two parameters of pressure and deformation are simultaneously measured in a decoupled manner. The compact and thin design of the sensor facilitates its integration into fingers or robotic digits, enabling assistance by deforming upon contact with materials and identifying their hardness through applied pressure. Separate performance tests of the two sensors show that the strain and pressure functions are decoupled from each other, and their ratios can identify and classify the hardness of different contact materials (glass, PDMS, and silicone). The hardness sensor can assist robots in operating human tissues during medical surgeries. The demonstrated fabrication and integration approaches provide a path toward tactile sensor applications in medical treatment, rehabilitation, services, and other processes.